Nutritional characteristics of bmr mutant and normal sorghum genotypes used for cutting and grazing - Poliana Batista de Aguilar; Daniel Ananias de Assis Pires; Benara Carla Barros Frota; José Avelino Santos Rodrigues; Sidnei Tavares Reis; Vicente Ribeiro Rocha Júnior (Acta Scientiarum. Animal Sciences, 2014)
This study evaluated the nutritional characteristics of BMR mutant and normal sorghum genotypes, eleven BMR mutants and nine normal. Seeds were sown in a randomized block design with three blocks, in which each genotype was a treatment. The nutritional characteristics were analyzed at 42 days of regrowth after the first cut, determined for DM, EE, ash, CP, NDIN, NIDA, NDF, ADF, NFC, CT, HCEL, CEL and NGLs. Regarding DM, EE, ash, NDIN, NIDA, NDF, FDA and HCEL, there were no differences between genotypes. As for CP, there were differences, with mean levels ranging from 9.77% for BR001AXTX2785bmr to 16.45% for BR001AxTX2784. Considering CT and NFC, there were differences in the mean levels that ranged from 75.21 to 83.28% for BR007AxTX2785bmr and BR001AXTX2785bmr, and from 17.46 to 25.51% for CMSXS156AxTX2785bmr and IS10428xTX2784, respectively. In relation to CEL and LGN significant difference were detected, the mean levels varied between 22.30 and 27.94% for the IS10428xTX2784 and TX635AxTX2785bmr, and from 3.08 to 7.31% for BR007AxTX2785bmr and BR001AxTX2784, respectively. The genotypes IS10428xTX2784 and BR007AxTX2784 are the most suitable for use in ruminant feed.